Coding and regulatory variants are associated with serum protein levels and disease - Emilsson, Valur; Gudmundsdottir, Valborg; Gudjonsson, Alexander; Jonmundsson, Thorarinn; Jonsson, Brynjolfur G.; Karim, Mohd A.; Ilkov, Marjan; Staley, James R.; Gudmundsson, Elias F.; Launer, Lenore J.; Lindeman, Jan H.; Morton, Nicholas M.; et al. (Nature communications, 2022)
Circulating proteins can be used to diagnose and predict disease-related outcomes. A deep serum proteome survey recently revealed close associations between serum protein networks and common disease. In the current study, 54,469 low-frequency and common exome-array variants were compared to 4782 protein measurements in the serum of 5343 individuals from the AGES Reykjavik cohort. This analysis identifies a large number of serum proteins with genetic signatures overlapping those of many diseases. More specifically, using a study-wide significance threshold, we find that 2021 independent exome array variants are associated with serum levels of 1942 proteins. These variants reside in genetic loci shared by hundreds of complex disease traits, highlighting serum proteins’ emerging role as biomarkers and potential causative agents of a wide range of diseases. Finding the genetic basis of protein expression can elucidate the genetic mechanisms of disease. Here, the authors link low-frequency and common DNA sequence variants to thousands of serum proteins, finding genetic overlap between circulating proteins and a wide range of common diseases.